2013
DOI: 10.1002/j.2161-1939.2013.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mindfulness and Meditation Practice on Client Perceptions of Common Therapeutic Factors

Abstract: Counselor mindfulness practice may help cultivate common therapeutic factors (e.g., empathy, working alliance). Researchers in this quantitative research study identified significant relationships between therapist mindfulness and client perceptions of the therapist's way of being and the working alliance. The impact of meditation training on these variables was also explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 54 publications
4
24
3
Order By: Relevance
“…Results of additional research indicated that a counselor’s ability to consistently develop strong working alliances with each client accounts for approximately 16% of client outcome (Baldwin, Wampold, & Imel, 2007; Wampold & Imel, 2015). In an attempt to identify counselor characteristics associated with forming and maintaining strong working alliances, some researchers have proposed mindfulness as one such characteristic (Christopher & Maris, 2010; Greason & Welfare, 2013; Hicks, 2010).…”
Section: The Working Alliancementioning
confidence: 99%
See 3 more Smart Citations
“…Results of additional research indicated that a counselor’s ability to consistently develop strong working alliances with each client accounts for approximately 16% of client outcome (Baldwin, Wampold, & Imel, 2007; Wampold & Imel, 2015). In an attempt to identify counselor characteristics associated with forming and maintaining strong working alliances, some researchers have proposed mindfulness as one such characteristic (Christopher & Maris, 2010; Greason & Welfare, 2013; Hicks, 2010).…”
Section: The Working Alliancementioning
confidence: 99%
“…These benefits include enhanced focus (Campbell & Christopher, 2012), management of intrusive thoughts and distracting internal emotional reactions (McCollum & Gehart, 2010), avoidance of negative evaluations of the client (Hicks, 2010), and improved recognition of and response to alliance ruptures (Safran & Muran, 2000). The results of prior research indicate that the working alliance has a positive association between dispositional mindfulness (Greason & Welfare, 2013; Ryan et al, 2012; Wexler, 2006) and state‐specific, in‐session mindfulness (Johnson, 2018). Researchers have also reported that client improvements are associated with dispositional counselor mindfulness (Ryan et al, 2012) and with counselor mindfulness practices (Grepmair et al, 2007).…”
Section: Mindfulnessmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this limitation, several authors have recommend identifying counselor characteristics associated with the consistent establishment of a strong working alliance (a component of successful therapeutic relationships; Baldwin et al, ; Del Re et al, ; Wampold & Imel, ) and fostering those identified characteristics in counselor education (Horvath, Del Re, Flückiger, & Symonds, ; Baldwin et al, ; Norcross & Lambert, ). Mindfulness may be one such characteristic (Christopher & Maris, ; P. R. Fulton, ; Greason & Welfare, ; Hicks, ).…”
mentioning
confidence: 99%